Reliability and Validity of the Korean Version of the Empathy Quotient Scale - Kim, JuHee (Korean Neuropsychiatric Association, 2010)
OBJECTIVE: The Empathy Quotient (EQ) is a self-reported test developed by Baron-Cohen et al. (2004) to measure the cognitive and affective aspects of empathy. The purpose of this study was to develop a Korean version of EQ and to establish its psychometric properties based on a representative Korean sample. METHODS: The Korean version of EQ and its correspondence with another popular measure of empathy, the Korean version of the Interpersonal Reactivity Index (IRI), were evaluated in a sample of 478 volunteers (156 men, 322 women; mean age, 27.2 years). A test-retest study was conducted at 1 month on a selected sample of 20 subjects from the original sample. Correlation and confirmatory factor analyses were conducted. RESULTS: The test-retest reliability was good, and the internal consistency was acceptable (Cronbach's alpha=0.78). Positive correlations were found between the EQ and three subfactors of the IRI, perspective taking, empathic concern, and fantasy, and the total EQ score was negatively correlated with the personal distress subscale. The confirmatory analyses suggested that the three-factor structure offered a good fit to the data. CONCLUSION: These findings support the reliability and validity of the Korean version of the EQ.